A postmodernist study of the internet - S.H. Heng, (Universiti Kebangsaan Malaysia, 1998)
This paper argues is that the activities associated with the Internet are organisational and societal activities taking place within a given historical context. As such explanations of these activities can profit from sociological theories such as postmodernism which can be seen as a reaction to some signal failures of modernism and the modernity project. Postmodernist thinking reflects both a sense of imposing crisis and a feeling that the modernist system of ideas no longer suffices. The sacrosanct notion of the privileged role of the enlightenment, rationality and reason has lost credibility. It is very much a socio-cultural and philosophical system of thoughts which sprouts in a post-industrial society. The relevant elements of postmodernism used here are: (a) power is diffuse, (b) there is no grand theory to make sense of reality; (c) the world is fragmented and chaotic, (d) information technology has an ambivalent character. It is argued that postmodernism offers a fruitful way of understanding and explaining the range of possibilities and challenges that accompany the advent of the Internet.